An Analysis of English Teachers Difficulties in Classroom Management at Seventh Grade of UPTD SMP Negeri 4 Gunungsitoli in 2023/2024 - Hulu, Melfan Widia Krisdayanti; Daeli, Hidayati; Harefa, Afore Tahir; Harefa, Trisman (ITScience (Information Technology and Science), 2024)
To effectively implement an independent curriculum, teachers must excel at engaging classroom management. This research aimed to identify challenges faced by English teachers in managing seventh-grade classes at UPTD SMP Negeri 4 Gunungsitoli and the factors contributing to these difficulties. A qualitative descriptive approach was used to gather data through classroom observations, teacher interviews, and student surveys. The data were analyzed to pinpoint specific challenges and their underlying causes. English teachers encountered nine primary classroom management issues, including difficulties in creating conducive learning environments, concluding lessons, managing transitions, and interacting with parents. Teachers also struggled with fostering a positive classroom community and providing effective rewards. Additionally, challenges arose in monitoring student progress, organizing group work, and assessing student performance. Teacher interviews revealed that time constraints, academic priorities, and limited school resources were major factors contributing to these difficulties. This study indicates that time, academic workload, and insufficient school resources significantly hinder English teachers' ability to manage their classrooms effectively within the independent curriculum framework.